Comparison of the Diversity of Weed Types in Oil Palm (Elaeis guineensis Jacq.) Plantations that have not been Replanted and After Replanting in PTPN II North Sumatera - Sari Anggraini; Lisa pebrianti (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Comparison of the Diversity of Weed Types in Oil Palm (Elaeis guineensis Jacq.) plantations that have not been replanted and after replanting in PTPN II, North Sumatra.". This study aims to determine the composition, structure of weed vegetation and the comparison of weed diversity in oil palm plantations before and after replanting. This study used a quadratic method with purposive sampling of weeds where the plots were 1 x 1 m in size with a total of 9 plots. The results of this study found that the composition of weeds on oil palm land before replanting was 12 families and 4 species, while on land after replanting there were 10 families and 5 species. The structure of weeds on the land before replanting with dominant weeds was Chrysopogon aciculatus (Retz) trin with an INP value (25,76%). was Ottochloa nodosa Kunth with an INP value (36.14%) while the lowest value was on weeds with an INP value (3.52%). on oil palm land after replanting the diversity value is I<H'<3